2008
DOI: 10.2527/jas.2008-0971
|View full text |Cite
|
Sign up to set email alerts
|

Fasting regulates the expression of adiponectin receptors in young growing pigs1

Abstract: Adiponectin is an adipocyte-derived hormone that can improve insulin sensitivity. Its functions in regulating glucose utilization and fatty acid metabolism in mammals are mediated by 2 subtypes of adiponectin receptors (AdipoR1 and AdipoR2). This study was conducted to determine the effect of fasting on the expression of adiponectin and its receptors. The expression of adiponectin was not affected in s.c. adipose tissue, but adiponectin expression increased in visceral adipose tissue after fasting. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
1
12
1
2
Order By: Relevance
“…Evidence for this assertion can be found in studies of various rodent models, where fasting, undernutrition and insulin deficiency lead to greater adiponectin sensitivity via increases in AdipoR expression [43,141,162]. In young growing pigs, fasting decreased the expression of T-cadherin but not AdipoR1/R2 in skeletal muscle [50]. On the other hand, adiponectin resistance resulted from decreased AdipoR expression under hyperglycemic and hyperinsulinemic conditions, in response to high-fat or high-sucrose feeding in rodent muscle and in genetically obese mice [141,158,161].…”
Section: Skeletal Musclementioning
confidence: 85%
See 2 more Smart Citations
“…Evidence for this assertion can be found in studies of various rodent models, where fasting, undernutrition and insulin deficiency lead to greater adiponectin sensitivity via increases in AdipoR expression [43,141,162]. In young growing pigs, fasting decreased the expression of T-cadherin but not AdipoR1/R2 in skeletal muscle [50]. On the other hand, adiponectin resistance resulted from decreased AdipoR expression under hyperglycemic and hyperinsulinemic conditions, in response to high-fat or high-sucrose feeding in rodent muscle and in genetically obese mice [141,158,161].…”
Section: Skeletal Musclementioning
confidence: 85%
“…AdipoR1 and AdipoR2 transcripts and proteins are both detected in mice skeletal muscle with a predominant expression of the AdipoR1 gene over AdipoR2 [50,141,158,161]. Moreover, the expression of AdipoR1/R2 in the skeletal muscle appears to be inversely regulated by insulin in physiological and pathophysiological states such as fasting/refeeding, insulin deficiency and hyperinsulinemia models and therefore correlates with adiponectin sensitivity.…”
Section: Skeletal Musclementioning
confidence: 91%
See 1 more Smart Citation
“…SMC abundantly express T-cad and can also shed MPs [40]. T-cad is also expressed in adipose tissue [41] and was very recently identified (by ESI-LC-MS/MS proteomic profiling) as a novel component of the secretome of adipocytes isolated from murine visceral adipose tissue [42]. Moreover, levels of T-cad were much less abundant in the secretome from diabetes-susceptible mice [42], which is concordant with the previous finding of lower levels of T-cad in diabetic patients as compared to patients without diabetes [19].…”
Section: Discussionmentioning
confidence: 99%
“…This laboratory has been interested in porcine adipose tissue lipid metabolism and its regulation, including studies of the cloned pAdipor1 and pAdipor2 . Our previous study found that both ADIPOR1 and ADIPOR2 were highly homologous between pigs and mice, and the receptors responded to insulin via the phosphatidylinositol 3-kinase (PI3K) pathway [10, 18, 19]. We have expressed the pADIPOR1 in mice in order to ascertain its metabolic functions and to be able to compare its functions to mADIPOR1.…”
Section: Introductionmentioning
confidence: 99%